2020
DOI: 10.1364/optica.397707
|View full text |Cite
|
Sign up to set email alerts
|

Fourier optical preprocessing in lieu of deep learning

Abstract: Deep learning convolutional neural networks generally involve multiple-layer, forward-backward propagation machine-learning algorithms that are computationally costly. In this work, we demonstrate an alternative scheme to convolutional neural nets that reconstructs an original image from its optically preprocessed, Fourier-encoded pattern. The scheme is much less computationally demanding and more noise robust, and thus suited for high-speed and low-light imaging. We introduce a vortex phase transform with a l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 57 publications
0
15
0
Order By: Relevance
“…We have previously shown that a convolutional neural network can outperform a single layer neural network but with significantly higher energy cost. The deep neural network is also less robust to noise [29]. Here, we aim to work with a "small brain" neural network rather than a deep neural network architecture.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We have previously shown that a convolutional neural network can outperform a single layer neural network but with significantly higher energy cost. The deep neural network is also less robust to noise [29]. Here, we aim to work with a "small brain" neural network rather than a deep neural network architecture.…”
Section: Discussionmentioning
confidence: 99%
“…In this section, we review an approach similar to [29] for our study of generalizable training. Figure 1(b) shows a schematic of the hybrid machine vision system, which encodes the image prior to the neural network with either a random or vortex phase pattern.…”
Section: Project Setupmentioning
confidence: 99%
See 1 more Smart Citation
“…[20][21][22][23][24][25][26] Using both optics and computation reduces time, power, memory, and complexity requirements; this hybrid approach may also provide additional information via a single sensor shot, which is useful for image enhancement. [27][28][29][30] In this communication, we show that multi-scaled structures with both material anisotropy and surface patterning may be employed for polarization-sensitive computer vision applications. Our insect-inspired design stems from knowledge of the corneal nanostructures on compound eyes, [2][3][4] which would optically shape and sort light via scattering.…”
Section: Introductionmentioning
confidence: 88%
“…This optical learning architecture achieved a high accuracy on the specific tasks (e.g., object classification and matrix-vector multiplication) close to in silico training on an electronic computer. Furthermore, there exist several studies on Fourier space image processing by optical neural network [124,131]. For instance, Yan et al [124] set up a Fourier space D 2 NN by placing an optical nonlinear activation function (introduced by ferroelectric thin films) in an 2f system (see Fig.…”
Section: Optical Diffractive Neural Networkmentioning
confidence: 99%